1984
DOI: 10.1104/pp.75.2.359
|View full text |Cite
|
Sign up to set email alerts
|

Photobiology of Diagravitropic Maize Roots

Abstract: Light-induced modification of gravitropism in etiolated roots of Zea nays cv Bear x W38 is a low fluence response mediated by phytochrome. This cultivar has a threshold of 10-' mol m2 and becomes saturated with 10-2 mol m-2 of red light. The maximum light-mediated response of 32 degrees downward from horizontal occurs in roots 10 to 30 millimeters in length, 120 to 165 minutes after irradiation. Reciprocity is valid from 2 to at least 9,000 seconds and the response can be about 90% reversed by far red light. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
28
1

Year Published

1987
1987
2000
2000

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 19 publications
1
28
1
Order By: Relevance
“…In some lines of corn, red light can shift the gravitropic responses ofroots from diagravitropic (seeking the horizontal) to orthogravitropic mode (seeking the direction of the earth) (6,7). The ability of added ABA to substitute for the red light (15), combined with the evidence that red light results in an increase in ABA in the roots (3) suggests that these two factors may influence similar components of the gravitropic system.…”
mentioning
confidence: 96%
“…In some lines of corn, red light can shift the gravitropic responses ofroots from diagravitropic (seeking the horizontal) to orthogravitropic mode (seeking the direction of the earth) (6,7). The ability of added ABA to substitute for the red light (15), combined with the evidence that red light results in an increase in ABA in the roots (3) suggests that these two factors may influence similar components of the gravitropic system.…”
mentioning
confidence: 96%
“…Suzuki and Fujii (8) were unable to reverse the promotive effects of R with a subsequent FR (730 nm) light treatment and therefore concluded that the gravitropic response in Zea roots ".may not be controlled by phytochrome." On the other hand, Shen-Miller (7) and later Mandoli et al (3) were able to prevent R-induced curving by following the R with FR. These workers concluded that light-induced gravitropism in maize roots was mediated by phytochrome.…”
mentioning
confidence: 99%
“…grow parallel or nearly parallel to the surface) (1,3,6,8). Illuminating these roots induces gravitropic curving, with R2 (660-670 nm) and to a lesser degree B (410-640 nm) particularly effective in promoting downward curving (1,3,(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…6). In a variety of plants, including a number of maize cultivars, root gravitropism is a light-regulated process wherein the primary roots of young, dark-grown seedlings grow plagiotropically (in a horizontal orientation) unless given a light pulse, whereupon they grow orthotropically (in a positively gravitropic fashion) (1 1, 16; earlier references reviewed in ref. 3).…”
mentioning
confidence: 99%